Peran Keraton Cirebon dalam Pembentukan Identitas Nasional pada Masa Kemerdekaan Indonesia: Analisis Politik Islam dan Nilai Nasionalisme - Muhammad Sungaidi; Aktobi Ghozali (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
This article explores the role of the Cirebon Keraton in shaping Indonesia’s national identity through the lens of Islamic politics and nationalist values. Based on interviews and historical data from the Cirebon Sultanate, the article analyzes how the sultans, particularly Sultan Muhammad Nurus, chose to align with the Unitary State of the Republic of Indonesia (NKRI) rather than maintain an independent kingdom. Using an Islamic political framework that emphasizes the concepts of khilafah (leadership), syura (consultation), adalah (justice), and maslahah (public welfare), the article demonstrates how the Cirebon Keraton’s decision reflects a commitment to unity, social justice, and the welfare of the people. The findings reveal that the Keraton’s role, both through diplomacy and contributions to the independence movement, has become an integral part of Indonesia’s pluralistic and inclusive national identity. This article also presents an analysis of the relationship between the central government and local entities in maintaining national stability and preserving cultural and political values.